2021
DOI: 10.3390/antibiotics10050530
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Use and Adverse Drug Reactions of Linezolid: A Retrospective Study in Four Belgian Hospital Centers

Abstract: In Belgium, linezolid is indicated for pneumonia and skin and soft tissue infections, but is more broadly used, due to its oral bioavailability and activity against multiresistant organisms. This could increase the risk of adverse drug reactions (ADR), notably hematological disorders (anemia, thrombocytopenia), neuropathy, or lactic acidosis. We analyzed linezolid clinical use in relationship with occurrence of ADR in Belgian hospitals and highlighted risk factors associated with the development of thrombocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 39 publications
(89 reference statements)
2
13
1
Order By: Relevance
“…Studies on the risk factors of LZD-associated thrombocytopenia suggest a relationship with renal function. 25,[28][29][30][31]36 In this study, S cr , CL cr , and LZD clearance values were also shown to be significant factors in the univariate analysis. However, we did not include them in the multivariate analysis as they were confounding factors associated with the safety target achievement rate calculated using parameters A and B.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Studies on the risk factors of LZD-associated thrombocytopenia suggest a relationship with renal function. 25,[28][29][30][31]36 In this study, S cr , CL cr , and LZD clearance values were also shown to be significant factors in the univariate analysis. However, we did not include them in the multivariate analysis as they were confounding factors associated with the safety target achievement rate calculated using parameters A and B.…”
Section: Discussionsupporting
confidence: 55%
“…This suggests that they are a risk factor for thrombocytopenia in patients undergoing LZD therapy (Tables 3 and 4). Studies on the risk factors of LZD‐associated thrombocytopenia suggest a relationship with renal function 25,28–31,36 . In this study, S cr , CL cr , and LZD clearance values were also shown to be significant factors in the univariate analysis.…”
Section: Discussionsupporting
confidence: 52%
“…A few studies have reported some risk factors in patients treated with linezolid for thrombocytopenia, such as poorer renal function, longer treatment duration, and the coexisting condition of malignancy. [8][9][10] Most studies conducted to date concerning this issue have always focused on adult populations, with only a few demonstrating the impact of linezolid use on the development of thrombocytopenia in pediatric patients. [11,12] Therefore, we conducted this study to investigate the relationship between linezolid use and severe thrombocytopenia and identify the potential risk factors for severe linezolid-associated thrombocytopenia in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of randomized clinical trials showed that the efficacy of linezolid for treatment of Gram-positive bacterial pneumonia was comparable to that of controls [ 2 ]. Linezolid-associated nephrotoxic effects are lower than those of vancomycin; however, with widespread clinical uses of linezolid, there are concerns about its platelet suppression effects, anemia induction, and other hematologic adverse effects [ 3 6 ]. Due to differences in design protocols and anemia definitions among studies, incidences of reported linezolid-associated adverse events have been shown to range from 14.1% to 64.7% [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Linezolid-associated nephrotoxic e ects are lower than those of vancomycin; however, with widespread clinical uses of linezolid, there are concerns about its platelet suppression e ects, anemia induction, and other hematologic adverse e ects [3][4][5][6]. Due to di erences in design protocols and anemia de nitions among studies, incidences of reported linezolid-associated adverse events have been shown to range from 14.1% to 64.7% [7][8][9].…”
Section: Introductionmentioning
confidence: 99%